A Tale of Two ‘Sities’ (Universities): Navigating Organisational and Operational Strategies in Higher Education Institutions - David FOWLER; Jon MUSGRAVE; Jill MUSGRAVE (Management and Economics Review, 2024)
This research endeavours to unveil the nuanced impact of organisational and operational models in higher education by conducting a comparative study of two institutions: the pseudonymous Old Orchard College and Seafarer University. The purpose is to discern the implications of adopting proven business strategies on institutional performance, growth, and student outcomes. The study employs a comprehensive methodology, integrating four years’ worth of personal observations, interviews with current and former employees, and rigorous data mining and analysis of government public domain databases. The comparative analysis delves into the organisational structures, academic focuses, and operational approaches of Old Orchard College and Seafarer University. The design embraces a multi-faceted approach to distill the complexities of organisational dynamics in higher education. The findings illuminate a stark dichotomy between the two institutions. Old Orchard College, undergoing an academic renaissance, is grappling with a shift in executive leadership and restructuring of academic responsibilities. In contrast, Seafarer University emerges as a model of efficiency, marked by its status as the fastest-growing state-supported university. The dialogue between tradition and innovation, and the transformative power of efficient organisational models, become focal points of discovery. This research contributes to the existing body of literature by providing an in-depth exploration of the impact of organisational paradigms on higher education institutions. The originality lies in the comparative nature of the study, which dissects the interplay between traditional and modern approaches. The inclusion of personal observations and data analysis adds a layer to the exploration, offering a holistic perspective on organisational dynamics in higher education.